Edukasi Dan Skrining Kesehatan Dalam Upaya Deteksi Awal Hipretensi, Kolesterol Dan Diabetes Melitus Di Masyarakat - Faris Alfizar; Desilia Sidong Liwu; Misbah Nurjannah; Musdalifah Rara Sanritama; Luthfiana Sukma Rantikasari; Salsa Nabila Putri Ramadini; Muhammad Izra Nurfadilla; Herniati Herniati; Sara Indrawati; Rozesky Ronald Octavian Sitorus (PELITA NUSA TENGGARA, 2026)
Community service activities through free health checks (CKG) in RT 08 Lok Bahu by Nursing Profession students of Muhammadiyah University of East Kalimantan were carried out as an effort to increase public awareness of the prevention of non-communicable diseases, especially hypertension and high cholesterol. The activity method consists of three stages, namely: the preparation stage, including initial health screening and data collection; the implementation stage in the form of health counseling, vital sign checks, as well as blood sugar, cholesterol, and uric acid checks; and the evaluation stage through feedback and assessment of the effectiveness of the activity. Of the 29 residents who participated, it was found that 14 people had hypertension and 10 people had high cholesterol levels, which indicates a high risk of cardiovascular disease in the area. The education provided was able to increase residents' understanding of the importance of a healthy lifestyle and early detection. Overall, this program was effective in increasing public health awareness and providing a preventive contribution to controlling hypertension and cholesterol.